2022
DOI: 10.3390/agronomy12020351
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen plus Sulfur Fertilization and Seeding Density on Yield, Rheological Parameters, and Asparagine Content in Old Varieties of Common Wheat (Triticum aestivum L.)

Abstract: Numerous epidemiological studies have highlighted the positive effects on health of wholegrain bakery products made from ‘old’ common wheat (Triticum aestivum L.) varieties. However, ‘old’ common wheat varieties display poor rheological properties, and there is limited information on its free asparagine (ASN) content, the main precursor to acrylamide during the baking process. This paper evaluates the effects of two seeding density levels (SD: 200 and 350 seed m−2), three nitrogen levels (NL: 35, 80 and 135 kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 47 publications
1
10
1
Order By: Relevance
“…The dynamics of nitrogen and its loss trend create a challenging environment for the effective management of this nutrient in topdressing [32], which is mainly due to various reactions and instability in the soil. The low efficiency of nitrogen is attributed to the volatilization, leaching, and surface runoff of ammonia [20]. Some studies have found the effects of sowing density and nitrogen on crops.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamics of nitrogen and its loss trend create a challenging environment for the effective management of this nutrient in topdressing [32], which is mainly due to various reactions and instability in the soil. The low efficiency of nitrogen is attributed to the volatilization, leaching, and surface runoff of ammonia [20]. Some studies have found the effects of sowing density and nitrogen on crops.…”
Section: Discussionmentioning
confidence: 99%
“…In wheat cultivation, sowing density and nitrogen fertilizer are critical factors affecting wheat population structure and yield formation [13][14][15][16]. Suitable sowing density can make wheat make full use of water, nutrients, and light energy [17,18], alleviate the competition between populations and individuals, and help to construct a reasonable population structure [19,20]. Rational use of nitrogen fertilizer can promote the healthy growth of wheat, improve grain quality, increase yield, and achieve sustainable development of agriculture [15,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that the content of an amino acid asparagine in the grain plays the key role in the acrylamide synthesis during the Maillard reaction, while the effect of dicarbonyl compounds, predominantly reducing sugars, is important, although, not crucial . Previous studies suggested that excess sulfur negatively affects asparagine synthesis in some cereals while promoting nitrogen synthesis (Soofizada et al ., 2022;Wilson et al ., 2020) . Studies have shown that in wheat grain, high content of free asparagine accumulates as a result of sulphur deficiency, poor disease control, and nitrogen fertilization (Curtis et al ., 2009;Curtis et al ., 2018) .…”
Section: Agronomic Approachmentioning
confidence: 99%
“…Similarly, grain yield, protein yield, and dough strength of wheat flour are significantly enhanced as S level increased. 14 However, crops often suffer from S deficiency in agronomic systems due to the use of S-free fertilizers, low S returns of farmyard manure, and S depletion in the soil. 15 Since S is required for the synthesis of proteins and enzymes, an insufficient S supply can affect the grain quality.…”
Section: ■ Introductionmentioning
confidence: 99%